2020
DOI: 10.2991/ijcis.d.200924.001
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Type Relations and Transformation Operators Defined by Monads

Abstract: Using the theory of monads in categories and the theory of monadic relations, the concept of general transformation operator defined by a monadic relation is introduced. It is proven that a number of standard relations used in categories of fuzzy structures are monadic relations for monads defined in these categories. It is also proven that a number of standardly used transformation operators in fuzzy sets, fuzzy rough sets, or fuzzy soft sets are in the form of general operators defined by monadic relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In this paper, we continued to build relational variants of categories K, i.e., such modifications of a category K, where instead of K-morphisms f : X → Y of this category, special relations R : X Y defined by a monad T in this category are considered. Then Kleisli category K T of a category K defined by a monad T can be considered as a relational variant of a category K. We first presented this type of transformation of a category K to relational version in [11], where we showed that many standard fuzzy type relations in various categories are in fact relations defined by monads and, therefore, categories with such defined relations as morphisms are isomorphic to Kleisli category.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, we continued to build relational variants of categories K, i.e., such modifications of a category K, where instead of K-morphisms f : X → Y of this category, special relations R : X Y defined by a monad T in this category are considered. Then Kleisli category K T of a category K defined by a monad T can be considered as a relational variant of a category K. We first presented this type of transformation of a category K to relational version in [11], where we showed that many standard fuzzy type relations in various categories are in fact relations defined by monads and, therefore, categories with such defined relations as morphisms are isomorphic to Kleisli category.…”
Section: Discussionmentioning
confidence: 99%
“…Example 2.3 [11] The monad G = (G, , ρ, 1 Set(L ) ) in the category Set(L ) is defined by 1. The object function G : Set(L ) → Set(L ) is defined by G(X, δ ) = (F(X, δ ), σ X,δ ), where the similarity relation σ is defined by…”
Section: Atlantis Studies In Uncertainty Modelling Volumementioning
confidence: 99%
See 3 more Smart Citations